How and why do win-win strategies work in engaging policy-makers to implement Health in All Policies? A multiple-case study of six state- and national-level governments - Lauri Kokkinen; Alix Freiler; Carles Muntaner; Ketan Shankardass (BMC, 2019)
Abstract Background Much of the research about Health in All Policies (HiAP) implementation is descriptive, and there have been calls for more evaluative evidence to explain how and why successes and failures have occurred. In this cross-case study of six state- and national-level governments (California, Ecuador, Finland, Norway, Scotland and Thailand), we tested hypotheses about win-win strategies for engaging policy-makers in HiAP implementation drawing on components identified in our previous systems framework. Methods We used two sources of data - key informant interviews and peer-reviewed and grey literature. Using a protocol, we created context-mechanism-outcome pattern configurations to articulate mechanisms that explain how win-win strategies work and fail in different contexts. We then applied our evidence for all cases to the systems framework. We assessed the quality of evidence within and across cases in terms of triangulation of sources and strength of evidence. We also strengthened hypothesis testing using replication logic. Results We found robust evidence for two mechanisms about how and why win-win strategies build partnerships for HiAP implementation - the use of shared language and the value of multiple outcomes. Within our cases, the triangulation was strong, both hypotheses were supported by literal and contrast replications, and there was no support against them. For the third mechanism studied, using the public-health arguments win-win strategy, we only found evidence from Finland. Based on our systems framework, we expected that the most important system components to using win-win strategies are sectoral objectives, and we found empirical support for this prediction. Conclusions We conclude that two mechanisms about how and why win-win strategies build partnerships for HiAP implementation - the use of shared language and the value of multiple outcomes - were found as relevant to the six settings. Both of these mechanisms trigger a process of developing synergies and releasing potentialities among different government sectors and these interactions between sectors often work through sectoral objectives. These mechanisms should be considered when designing future HiAP initiatives and their implementation to enhance the emergence of non-health sector policy-makers' engagement.